Mediation In Construction Industry? - Ismail, Zulhabri; Abdullah, Jamalunlaili; Hassan, Padzil Fadzil; Mohamad Zin, Rosli (Journal of Surveying, Construction and Property, 2010)
Private dispute resolution refers to settlement of disputes â€œother than litigationâ€ which is not open to the public. This includes mediation, adjudication and arbitration. Of the three private dispute resolution methods, arbitration and mediation were promoted in the Malaysian construction industry. Notwithstanding the continuing reliance on litigation as the approach to solve construction disputes, arbitration was gradually accepted by the industry. As arbitration is a more favored approach, it was realized that arbitration can be adversarial. Therefore, a more â€œfriendlyâ€ approach to solve disputes was needed to be considered. Consequently, mediation was introduced and promoted. However to date, its application has been poor. This paper presents the research which investigates what is currently the trend in mediation. It was developed on the premise that the poor response in adopting mediation as a form of private dispute resolution could be because mediation was poorly conceived and applied. A combined quantitative research method using the survey and qualitative research method using semi-structured interviews were adopted for the research. The variables which could impact on the application of mediation were also investigated. The findings suggested that, while mediation was generally considered appropriate there were concerns on the adequacy of its provisions and practice. Views on how this could be overcome were identified. The conclusions suggested the needs for the industry to re-learn its approach in the promotion and the application of mediation if it is to be more effective.